RARE TUMOR OF THE STOMACH: SOLITARY FIBROUS TUMOR – A CASE REPORT - Bošković, Tamara J; Živojinov, Mirjana; Ilic Sabo, Jelena R; Veljković, Radovan; Budakov, Zorana; Živojinov, Srđan (Vojnosanitetski pregled, 2015)
Introduction: Solitary fibrous tumors are rare soft tissue tumors submesothelial origin variable malignant potential. The most common localization is pleural, whereas only 0.6% are extra pleural localization. Solitary fibrous tumor of the peritoneum, especially of gastric serosa is a extremely rare form of this tumor. Case report: This paper presents the case of a patient aged 65. Histopathological analysis of removed tissue showed the presence of tumor tissue built of spindle cells, elongated nuclei with moderately abundant cytoplasm. Cells are in a non-cohesive arrangement, in smaller areas distributed in the form of palisade. There are amount of hipocellular connective tissue, hyalinised, with small foci of dystrophic calcification. Mitoses are rare (less than 3/10 HPF). Blood vessels surround the connective tissue. Reviewed material does not contain elements of the parent organ. Immunohistochemically there is positivity on CD34 and vimentin, negativity on S100, SMA, CD117, dezmin, and Ki-67 is <2%. Change was diagnosed as a solitary fibrous tumor. Conclusion: Extra thoracic solid fibrous tumors show mainly the biological behavior of benign soft tissue tumors, with greater ability to recur with local destruction or in the form of distant metastasis. It is extremely important to make the proper diagnosis, as well as clinically control the patients.